Temporal variations of soil saturated hydraulic conductivity under different land use types and its impact on water balance components - Tianqi Guo; Yalin Ji; Xiaoying Yan; Ahmed Yehia Mady; Rui Liu; Mingbin Huang (Agricultural Water Management)
Soil saturated hydraulic conductivity (Ks) is one of the important soil hydraulic properties impacting the dynamic changes in soil water content and water balance components. Determining the impact of the temporal variation of Ks on these components is helpful for water resource management on the Chinese Loess Plateau. The main objective of this work was to estimate the efficiency of dual-porosity model in Hydrus-1D for simulating soil water content and water balance components with and without the temporal variation of Ks. Moreover, the effect of temporal variation of Ks on water balance components was estimated under different land use types. In this study, the double ring infiltrometers were used to measure Ks values for corn field and forestland sites from April to October 2022. The dynamic changes of soil water content and water balance components for both land use types were simulated using the calibrated and validated dual-porosity equations in the Hydrus-1D model under the two scenarios: (1) constant Ks, an average over the whole measuring period, and (2) temporally variable Ks. The results showed the temporal variation of Ks was significant for the corn field site due to tillage and not significant for the forestland site due to the lack of disturbance. The accuracy of the dual-porosity equations in the Hydrus-1D model increased by 14 % for the corn field site but by only 5 % for the forestland site when considering temporally varying Ks vs. constant Ks. In addition, the temporal variation of Ks resulted in evaporation increasing by 1.27 %, deep percolation decreasing by 14.92 %, and no obvious changes in transpiration and soil water storage of 300 cm for the corn field site, while almost consistent water balance components for the forestland site for both scenarios. These results indicated the temporal variation of Ks should be considered to improve simulations of soil water content and water balance components, particularly in farmland, which are useful for managing soil and water resources.